2009
DOI: 10.1353/cpr.0.0081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Partnership Approach to Translating Research on Breast Cancer and the Environment

Abstract: Background-The growing literature on community-based participatory research (CBPR) suggests that a participatory approach benefits science in important ways. However there have been few formal evaluations of a CBPR approach itself, and few standards developed to assist in such efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…In 2008, these guidelines were further refined and reliability was tested to develop the Reliability Tested Guidelines for Assessing Participatory Research Projects [ 13 ] as a tool to (i) help funding agencies and peer reviewers to assess the participatory nature of proposals submitted for funding as participatory research; (ii) aid evaluators in assessing the extent to which projects meet participatory research criteria; and (iii) assist researchers and intended users of the research (i.e., nonacademic partners) in strengthening the participatory nature of their project proposals and applications for funding [ 12 , 13 ]. In 2009 van Olphen et al [ 14 ] applied these guidelines for the first time, to a single project to assess to what extent their research was participatory as perceived by community, advocacy, and scientific partners. The authors concluded that this had been a very useful undertaking and that “further research should focus on the adaptation of PR principles to assist in evaluating the process and outcomes of PR [ 14 ].”…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, these guidelines were further refined and reliability was tested to develop the Reliability Tested Guidelines for Assessing Participatory Research Projects [ 13 ] as a tool to (i) help funding agencies and peer reviewers to assess the participatory nature of proposals submitted for funding as participatory research; (ii) aid evaluators in assessing the extent to which projects meet participatory research criteria; and (iii) assist researchers and intended users of the research (i.e., nonacademic partners) in strengthening the participatory nature of their project proposals and applications for funding [ 12 , 13 ]. In 2009 van Olphen et al [ 14 ] applied these guidelines for the first time, to a single project to assess to what extent their research was participatory as perceived by community, advocacy, and scientific partners. The authors concluded that this had been a very useful undertaking and that “further research should focus on the adaptation of PR principles to assist in evaluating the process and outcomes of PR [ 14 ].”…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 van Olphen et al [ 14 ] applied these guidelines for the first time, to a single project to assess to what extent their research was participatory as perceived by community, advocacy, and scientific partners. The authors concluded that this had been a very useful undertaking and that “further research should focus on the adaptation of PR principles to assist in evaluating the process and outcomes of PR [ 14 ].”…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive CBPR evaluation must include other methods such as the use of focus groups, individual interviews, ethnographic observations, and other documentation from university and community stakeholders. 25 However, development of a quantitative tool that is easy to use is important for CBPR projects that lack the resources to collect in-depth qualitative data and allows for some standardization of how CBPR is measured across projects.…”
Section: Discussionmentioning
confidence: 99%
“…Asking community partners to complete the tool would allow comparison of community and academic perspectives (although Van Olphen et al had a low response rate from community partners when she asked them to complete her CBPR questionnaire). 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation